BUDAYA HUKUM DALAM KEBERLAKUAN UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA PADA PENGRAJIN PERAK DI BALI - Mahadewi, Kadek Julia (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 4 No 2 (2015), 2015)
The Law No.28 year of 2014 regarding Copyright set about the protection of copyright works,one form of copyright works which is being protected is silver handicrafts.In Bali it is popular for its silver handicrafts which its motif is unique and creative so that the existence of silver handicrafts can penetrate international and domestic market.Silversmiths in Bali in producing works of silver handicrafts,in which they found the problem that they had to face such as the case that fallen upon silversmiths in creating their works as follows,first,there were the products of Balinese silver handicrafts registered its copyright by foreign party.The case was experienced by Desak Nyoman Suarti against Lois Hill the businessman from USA.Second,it is accused toward Balinese silversmith that he copied silver handicraft’s copyright owned by foreign party,it was happening toward Balinese craftsman Ketut Deni Aryasa against John Hardy the owner of PT.Karya Tangan Indah.It certainly harms Balinese silversmiths when the truth is that silver handicrafts can be protected by Copyright Law No.28 year of 2014 in the article of 38.From the issues mentioned above we conducted the research titled: Legal Culture in the Enforceability of the Law No.28 year of 2014 Regarding Copyright of the Balinese Silversmiths. The type of this research belonged to the study of empirical law. The result of research shows that, first, the type of law protection provided by the state towards traditional motifs is in the form of preventive and repressive law protection. Second, legal culture of silversmiths in Bali view traditional motifs as a work substance with work orientation is for a living so that value system being adopted by most silversmiths in Bali is not to register their works into the Copyright system.
Keywords: Legal Culture; the Enforcement of Copyright Law; Balinese Silversmi